PENGARUH BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. BANK MANDIRI CABANG PALEMBANG - Kamariah Kamariah; Herlan Junaidi (Fakultas Ekonomi Universitas Tridinanti Palembang, 2021)
The purpose of this study was to determine the Effect of Organizational Culture and Work Discipline on Employee Performance at PT. Bank Mandiri Palembang Branch, Tbk. The variables used in this study, Organizational Culture (X1), Work Discipline (X2), Employee Performance (Y). The population in this study were employees of PT. Bank Mandiri Palembang Branch, Tbk, amounting to 40 people. This type of research is quantitative. The research technique used is multiple linear regression, hypothesis testing, F test and t test.The regression results obtained the equation Y = 3.430 + 0.637 X1 + 0.263 X2. Which means that Employee Performance is influenced by Organizational Culture and Work Discipline. F test results obtained significance less than 0.05 (0,000 <0.05), meaning that there is an influence of Organizational Culture and Work Discipline simultaneously on Employee Performance. The t test results of Organizational culture variables obtain significance less than 0.05 (0.000 <0.05), meaning that there is an partial influence of Organizational Culture on Employee Performance, and Work Discipline variables obtain significance less than 0.05 (0.006 <0, 05), meaning that there is a partial influence of Work Discipline on Employee Performance.